2003
DOI: 10.1124/jpet.103.053421
|View full text |Cite
|
Sign up to set email alerts
|

Ginger Reduces Hyperglycemia-Evoked Gastric Dysrhythmias in Healthy Humans: Possible Role of Endogenous Prostaglandins

Abstract: Acute hyperglycemia evokes gastric slow wave dysrhythmias via endogenous prostaglandin generation. Ginger exhibits slow wave antiarrhythmic effects in other models, but its actions on hyperglycemia-evoked gastric dysrhythmias are unexplored. We hypothesized that ginger prevents disruption of slow wave rhythm by acute hyperglycemia via inhibition of prostaglandin production but not its actions. Twenty-two healthy humans underwent fasting electrogastrography during hyperglycemic clamping to 250 to 290 mg/dl afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 32 publications
1
16
0
3
Order By: Relevance
“… 22 Since then, numerous studies have reported gastric dysrhythmias, mostly tachygastria, in various clinic settings, such as gastrointestinal motility disorders, 23 motion sickness 24 and early pregnancy 25 and surgical procedures 26,27 . Tachygastria can be induced experimentally with various chemical agents and gastrointestinal hormones or peptides, such as prostaglandin, 28 vasopressin, 29 glucagon, 30 atropine, 31 nicotine 32 and insulin, cholecystokinin‐pancreozymine, and pentagastrin 33 …”
Section: Discussionmentioning
confidence: 99%
“… 22 Since then, numerous studies have reported gastric dysrhythmias, mostly tachygastria, in various clinic settings, such as gastrointestinal motility disorders, 23 motion sickness 24 and early pregnancy 25 and surgical procedures 26,27 . Tachygastria can be induced experimentally with various chemical agents and gastrointestinal hormones or peptides, such as prostaglandin, 28 vasopressin, 29 glucagon, 30 atropine, 31 nicotine 32 and insulin, cholecystokinin‐pancreozymine, and pentagastrin 33 …”
Section: Discussionmentioning
confidence: 99%
“…Ginger also prolonged latency before nausea onset and shortened recovery time after exposure to a rotating optokinetic drum, a stimulus that often induces symptoms of motion sickness. Gonlachanvit et al 10 reported that one gram of ginger reduced the gastric dysrhythmia and nausea resulting from the infusion of dextrose to produce hyperglycemia in healthy humans. In addition, it has been shown that ginger reduces postoperative nausea and vomiting.…”
Section: Introductionmentioning
confidence: 98%
“…Alternative therapies include ginger [133] , acupuncture with stimulation of the PC6 point on the wrist [134,135] , or the ST36 (Zusanli) point below the patella [136] .…”
Section: Gastroparesismentioning
confidence: 99%